Pengaruh Dewan Komisaris Independen dan Komite Audit terhadap Tax Avoidance Perusahaan LQ45 - Felicia Artamevia; Shella Nur Afifah; Erlina Sari; Naurah Alifia Putri Wicaksono; M. Zainul Abidin; Rohmawati Kusumaningtias; Ambar Kusumaningsih (Jurnal Ilmiah Aset, 2026)
This study aims to analyze the influence of the independent board of commissioners and audit committees on tax avoidance practices in companies that are members of the LQ45 index for the 2022–2024 period. The background of the research is based on the still high practice of tax avoidance that takes advantage of regulatory loopholes and the importance of good corporate governance mechanisms in supervising management policies. This study uses an explanatory quantitative approach with secondary data in the form of financial statements and annual reports. The sample was determined through purposive sampling and obtained from 28 companies. The dependent variable of tax avoidance is measured using the Effective Tax Rate (ETR), while the independent variable includes the proportion of the independent board of commissioners and the number of audit committees. Data analysis was carried out by multiple linear regression after going through the classical assumption test. The results of the study show that independent board of commissioners has a negative and significant effect on tax avoidance, which means that the higher the proportion of independent commissioners, the more tax avoidance practices tend to decrease. On the other hand, audit committees have a positive and significant effect on tax avoidance, which shows that an increase in the number of audit committee members does not necessarily increase the effectiveness of supervision. These findings indicate that the effectiveness of surveillance is determined not only by quantity, but also by quality and independence. Therefore, companies need to strengthen their supervisory function substantively to suppress tax avoidance practices.